2017
DOI: 10.3346/jkms.2017.32.2.272
|View full text |Cite
|
Sign up to set email alerts
|

The Curves Exercise Suppresses Endotoxemia in Korean Women with Obesity

Abstract: Obesity and metabolic syndrome is a worldwide pandemic and associated with high cardiovascular risk. Metabolic endotoxemia (ME) is thought to be an underlying molecular mechanism. It triggers toll-like receptor 4-mediated inflammatory adipokines and causes a chronic low grade inflammatory status, which results in cardiovascular risk increase. Exercise is the best nonpharmacological treatment to improve prognosis. In this study, we examined the circulating endotoxin level in Korean obese women and investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…6 and Supplementary Table 6 ). This result agreed with previous findings in Korean women 38 . Among FMT recipients, the reduced expressions of Tlr4 and Nod2 compared to H reflected lower inflammation (Supplementary file: Supplementary Fig.…”
Section: Discussionsupporting
confidence: 94%
“…6 and Supplementary Table 6 ). This result agreed with previous findings in Korean women 38 . Among FMT recipients, the reduced expressions of Tlr4 and Nod2 compared to H reflected lower inflammation (Supplementary file: Supplementary Fig.…”
Section: Discussionsupporting
confidence: 94%
“…[363][364][365] Twelve weeks of circuit-style resistance training has been shown to decrease postprandial endotoxin concentrations by 17% following high-fat meal consumption in cisgendered women with obesity. 366 Unfortunately, there are limited studies examining the effects of exercise training on intestinal permeability and microbial translation in PLWH on ART. Troseid et al 367 reported that neither 16 weeks of resistance or endurance training significantly reduced LPS concentrations in PLWH, although changes in LPS correlated with changes in triglycerides.…”
Section: Exercise On Intestinal Permeability and Microbial Translocationmentioning
confidence: 99%